2006
DOI: 10.2323/jgam.52.47
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the microbial diversity in cold-seep sediments from different depths in the Nankai Trough

Abstract: We have investigated the molecular phylogeny of cold-seep sediments obtained from the Nankai Trough, at depths of about 600, 2,000, and 3,300 m, and compared the microbial diversity profiles of those sediments samples. The g g-Proteobacteria that might function as sulfide oxidizers and the symbiotically related d d-Proteobacteria which might function as sulfate reducers were identified amongst the bacteria from all depths of the sediments. However, anoxic methane oxidizing archaea (ANME) and methanogens were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 17 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…Geographic distribution of AOM in association with gas hydrates or other methane-rich environments is widespread, which includes the Black Sea (Wakeham et al 2004;Leloup et al 2007), Cascadia margin (Cragg et al 1996;Bidle et al 1999;Marchesi et al 2001;Knittel et al 2005;Lanoil 2005;Inagaki et al 2006), Eel River Basin (Hallam et al 2003), Guaymas Basin (Teske et al 2002;Dhillon et al 2003), Gulf of Mexico (see below), Japan Trench (Li et al 1999;Inagaki et al 2002), Mediterranean Sea (Heijs et al 2005(Heijs et al , 2007Kormas et al 2005), and Nankai Trough (Newberry et al 2004;Arakawa et al 2006). In the Gulf of Mexico, microbiological studies of gas hydrates have been performed in the Green Canyon (GC), Atwater Canyon (AT), Keathley Canyon (KC), Garden Bank (GB) and Mississippi Canyon (MC).…”
Section: Introductionmentioning
confidence: 95%
“…Geographic distribution of AOM in association with gas hydrates or other methane-rich environments is widespread, which includes the Black Sea (Wakeham et al 2004;Leloup et al 2007), Cascadia margin (Cragg et al 1996;Bidle et al 1999;Marchesi et al 2001;Knittel et al 2005;Lanoil 2005;Inagaki et al 2006), Eel River Basin (Hallam et al 2003), Guaymas Basin (Teske et al 2002;Dhillon et al 2003), Gulf of Mexico (see below), Japan Trench (Li et al 1999;Inagaki et al 2002), Mediterranean Sea (Heijs et al 2005(Heijs et al , 2007Kormas et al 2005), and Nankai Trough (Newberry et al 2004;Arakawa et al 2006). In the Gulf of Mexico, microbiological studies of gas hydrates have been performed in the Green Canyon (GC), Atwater Canyon (AT), Keathley Canyon (KC), Garden Bank (GB) and Mississippi Canyon (MC).…”
Section: Introductionmentioning
confidence: 95%
“…Halobacteria and MBG-B were dominant archaeal communities in the abyssal cold seep at a water depth of 3,000 mbsf in Core DSH-1 (ZHANG et al 2012). However, MGI and ANME archaeal groups were dominant in cold seep surface sediments from the Nankai Trough along the western margin of the Pacific Ocean (ARAKAWA et al 2006). In the Gulf of Mexico hydrocarbon seep, Methanosarcinales, ANME-1, Thermoplasmales and Methanomicrobiales were found to be dominant (MILLS et al 2003), and ANME was the dominant group in the Sonora Margin cold seeps in Guaymas Basin (Gulf of California) (VIGNERON et al 2013).…”
Section: Archaeal Community Variation and Geobiochemical Reactionsmentioning
confidence: 91%
“…It was demonstrated that methanotrophic archaea carry out a process called anaerobic oxidation of methane (AOM), initiating the living processes of growth, reproduction and energy flow to make other organisms' existence possible. Considerable research of archaeal communities has been conducted in different typological cold seep areas around the world, such as Hydrate Ridge (KNITTEL et al 2005), Nankai Trough (ARAKAWA et al 2006), Tropical Timor Sea (WASMUND et al 2009), Northern South China Sea (Northern SCS) (ZHANG et al 2012), and Sonora Margin (VIGNERON et al 2013). These studies showed that different cold seep areas harbored different archaeal communities.…”
Section: Introductionmentioning
confidence: 99%
“…These sequences are affiliated with uncultivated Archaea from deep-sea sediments in the Weddell Sea (Brandt et al, 2007), the East Pacific Rise (Mason et al, 2007), the Nankai Trough (Arakawa et al, 2006), the Pacific nodule province (Xu et al, 2005), the Peru margin , the Eastern Mediterranean (Heijs et al, 2008) and the North Atlantic (Agogue et al, 2008). Phylotypes pTVGA19 and 37 shared 96% similarity with a clone obtained from sediment present in a tropical seawater tank at the Seattle Aquarium, which was closely related to Nitrosopumilus maritimus SCM1, the first cultured mesophilic representative of the Crenarchaeota belonging to the MGI group (Könneke et al, 2005).…”
Section: Archaeal Diversitymentioning
confidence: 98%
“…Numbers in the Venn diagrams indicate number of OTUs. Ridge (Schrenk et al, 2004), and clone pTVGA24 was distantly related to MGI clone ANT33-04 (Arakawa et al, 2006).…”
Section: Archaeal Diversitymentioning
confidence: 98%